A case study of topographical disorientation: behavioural intervention for achieving independent navigation. Issue 5 (4th July 2018) - Rivest, Josée; Svoboda, Eva; McCarthy, Jeff; Moscovitch, Morris
ABSTRACT: This study introduces an intervention that enabled a man (LH) with acquired topographical disorientation (TD) to travel independently without fear of getting lost. Adapting an errorless method, LH learned to use a smartphone to find his routes accurately and reliably. A time-series design (A1 -B1 -A2 -B2 ) was used: In all phases, LH was given a printed map on which city locations were indicated. He had to walk to the indicated locations while naturalistic outcomes were recorded. In Phases A, he navigated without his smartphone, and in Phases B, with it. In Phases A, LH made numerous surplus direction changes, and openly expressed his frustration. In Phases B, he did not have surplus direction changes and could calmly find his routes. Before intervention, LH and his wife were frustrated and worried about his way-finding. They rated their confidence in his navigational ability and his actual ability in way-finding to various locations as low. After intervention, they were more confident that LH could travel by himself without getting lost and rated his ability as much higher for various scenarios. As a consequence of intervention LH gained greater independence and quality of life.